Understanding contemporary images using iconography: Migration to the European Union and the representation of refugees and asylum seekers. Issue 2 (2nd April 2020) - Clark, Serena
Abstract: Attaining visual literacy is becoming of growing importance, and iconography is an approach that allows people to become visually literate. Globalisation and technological advancements have transformed the way people communicate and understand the social and political realities that inform their everyday lives. The generation of information that guides these realities has become progressively more visual and accessible to a global audience. People's visual worlds have expanded to incorporate those that are not part of their environments. The increasing interconnectedness of the world and the rapid dissemination of information through visual mediums make visual literacy important and iconography relevant. This article explores the use of iconography to understand images and provides a framework for exploring their meaning. To accomplish this goal, iconography is discussed alongside the issue of migration to the European Union and the image of Alan Kurdi.